Factors influencing the competitiveness of aviation companies - D. E. Aubakirova; G. N. Jaxybekova (Экономика: стратегия и практика)
Over the past twenty years, the airline industry has grown significantly, its growth rate exceeds the growth rate of world nominal GDP. Increasingly growing competition in the air transport market obliges airlines to provide their customers with quality products and services. In this regard, now the main goal of the airline is to increase its competitiveness, on which its image, economic results and development prospects depend.The article examines the factors affecting the competitiveness of airlines, a comparative analysis of the competitiveness factors of various objects of research is carried out: the domestic airline Air Astana with the largest airlines in the world - Aeroflot and Ural Airlines (RF) (RF), Belavia (Ukraine), Lufthansa (Germany), Turkish Airlines (Turkey).The purpose of the study is to justify the economic content and classification of the “competitiveness” category, score and the relationship of factors affecting the competitiveness of an air transport company.The article used qualitative and economic-statistical research methods. Qualitative methods are based on a scoring system, economic and statistical methods (correlation-regression model) are based on quantitative data of various factors that affect the competitiveness of airlines.The results of the study are the classification and justification of the external and internal competitiveness factors of civil aviation companies, the key ones of which, in our opinion, are the number of passengers and cargo transported, the size of the fare, staff efficiency, financial performance indicators of aviation companies, and the development of correlation and regression models that revealed a positive impact of Air Astana’s passenger traffic (87%) and assets (46%) on their revenues.